A Corporate Beauty Contest - Graham, John R.; Harvey, Campbell R.; Puri, Manju (Management Science, 2017)
We provide new evidence that the subjective “look of competence” rather than beauty is important for CEO selection and compensation. Our experiments, studying the facial traits of CEOs using nearly 2,000 subjects, link facial characteristics to both CEO compensation and performance. In one experiment, we use pairs of photographs and find that subjects rate CEO faces as appearing more “competent” than non-CEO faces. Another experiment matches CEOs from large firms against CEOs from smaller firms and finds large-firm CEOs look more competent. In a third experiment, subjects numerically score the facial traits of CEOs. We find competent looks are priced into CEO compensation, more so than attractiveness. Our evidence suggests this premium has a behavioral origin. First, we find no evidence that the premium is associated with superior performance. Second, we separately analyze inside and outside CEO hires and find that the competence compensation premium is driven by outside hires—the situation where first impressions are likely to be more important. This paper was accepted by Lauren Cohen, finance.